Local temperature near native vascular plants in the Argentine Islands–Kyiv Peninsula region, Antarctic Peninsula: annual variability and approximation using standard meteorological measurements - Mykhailo V. Savenets; Larysa Pysarenko; Svitlana Krakovska; Ivan Parnikoza; Denys Pishniak (Polar Research, 2023)
We describe the main features of LT variability that influence native vascular plants in the Antarctic and examine the relationship between the temperature regime at the micro-level and meteorological conditions at the macro-level. We used a period of over a year, during which 37 specialized mini-loggers recorded LT near vascular plants in the Argentine Islands–Kyiv Peninsula region of the Antarctic Peninsula. Rather than measuring standard air or soil temperature, these loggers detect the temperature near the ground, in the microhabitats that harbour vascular plants. On a daily scale, LT correlates with standard (2-m) air temperature, with the values higher at rock slopes than at rock terraces and ledges. A moderate correlation was found with wind and radiation parameters. Seasonality accounted for 75–93% of total LT variability, with better results on open rock terraces compared to protected areas and clefts. LT day-to-day variability during the cold season is mostly responsible for differences in R2 of the annual cycle. We estimated daily mean LT using regression dependencies from 2-m air temperature and wind speed measured at a nearby meteorological station. R2 for these statistical models varies from 0.46 to 0.68. However, they underestimate the observed LT. LT measured on rock slopes showed better modelling results with air temperature, whereas wind speed was a better predictor on rock ledges. This study contributes to our understanding of the micro-scale temperature regime that influences native vascular plants and provides a method for its rough approximation using standard meteorological parameters.